DESAIN STRATEGI BISNIS PADA UMKM JAJANAN MANTAN DAN PRENCHIPS - Mutqi Sopiawadi; Tigin Lugiani; Panji Agnyoto; Jojo Jojo (STIESA-PRESS, 2024)
The aim of this research is to produce a design for the formulation and implementation of business strategies for MSMEs for former snacks and prenchips with the method used in this research, namely using qualitative methods with data sources obtained from the results of discussions and interviews with the owner. The results of the SWOT matrix analysis, the vision, mission and strategy of the MSMEs for Former Snacks and Prenchips was born, namely, the vision is to be able to export products abroad and to become a vehicle that can help other people to do business too. To achieve this vision, MSMEs Snacks Former and Prenchips strive to provide extra quality products and offer more menu variants. And from the results of the matrix analysis, the MSMEs of Former Snacks and Prenchips in making the program refer to growth strategies, growth in the quality of human resources, growth in asset value, sales growth, and the number of products that have been innovated, new and more varied food menus. The MSME program for Former Snacks and Prenchips emphasizes programs for human resources and marketing, throughout these programs the percentage of the MSME Snacks Former and Prenchips budget for one year is greater for improving financial programs, and the remainder for operational production, marketing and quality improvement programs. tbsp.